Results of Intramedullary Nailing at Tibia Distal Hypertropic Nonunions - Demir, Şükrü; Gürger, Murat; Önce, Gökhan; Batur, Ömer Cihan; Key, Sefa (Kahramanmaras Sutcu Imam University, 2022)
Abstract Objective: Nonunion is a common problem in fractures in the lower third of the tibia. Conditions such as thin soft tissue cover and poor blood supply cause this situation. In addition, mechanical problems such as proximity to the ankle and short distal segment makes the treatment of nonunion very difficult. Intramedullary nailing offers a powerful solution to this problem. Because there is no need for wide dissection and the implant remains intraosseous, creating a minimum problem for soft tissues. The aim of this study is to determine the efficacy of reamed intramedullary nail in the treatment of nonunions developed in fractures in the lower 1/3 of the tibia. Material and Methods: The data of 14 patients who developed nonunion after a fracture of the lower 1/3 tibia and were treated with a reamed intramedullary nail were retrospectively analysed. All patients whose fractures in the 1/3 distal of the tibia and who did not have any signs of active infection were included in the study. Two patients had a history of superficial infection occurring after the first operation, but none of the patients had signs of active infection during the operation. All patients were treated with reamed locked intramedullary nailing. Results: Union was achieved in all patients. Mean time to union was 5.7 (3-10) months. No patient developed an infection. Conclusion: Reamed locked intramedullary nailing is a very reliable method in the treatment of nonunions, which are seen in the lower third of the tibia and are difficult to treat.

Özet Amaç: Tibianın alt 1/3 lük kısmında gelişen kırıklarda kaynamama sık karşılaşılan bir problemdir. Bu durumua ince yumuşak doku örtüsü ve zayıf kanlanma gibi durumlar sebep olurlar. Ayrıca ayak bileğine yakınlık ve kısa distal segment gibi mekanik problemler kaynamama probleminin tedavisini oldukça güçleştirir. İntramedüller çivileme, bu soruna güçlü bir çözüm sunar. Çünkü geniş diseksiyona gerek kalmaz ve implant intraosseöz kalarak yumuşak dokular için minimum problem oluşturur. Bu çalışmanın amacı, tibianın alt 1/3 lük kısmındaki kırıklarda gelişmiş olan kaynama kusurlarının tedavisinde oyulmuş intramedüller çivinin etkinliğini belirlemektir. Gereç ve Yöntemler: Tibia alt 1/3’lük bölge kırığı sonrasında kaynamama gelişen ve sonrasında oymalı intramedüller çivi ile tedavi edilen 14 hastanın verileri retrospektif olarak incelendi. Çalışmaya tibia 1/3 distalindeki kırığı kaynamayan ve aktif enfeksiyon bulgusu olmayan tüm hastalar dahil edildi. İki hastada ilk operasyon sonrası ortaya çıkan yüzeysel enfeksiyon öyküsü vardı, ancak ameliyat sırasında hiçbir hastada aktif enfeksiyon belirtisi yoktu. Tüm hastalar oymalı kilitli intramedüller çivileme ile tedavi edildi. Bulgular: Hastaların hepsinde kaynama elde edildi. Ortalama kaynama süresi 5.7 (3-10) ay idi. Hiçbir hastada enfeksiyon gelişmedi. Sonuç: Oymalı kilitli intramedüller çivileme, tibianın alt 1/3’lük bölgesinde görülen ve tedavisi oldukça güç olan kaynamamaların tedavisinde gayet güvenilir bir yöntemdir.
Tibia Distal Hipertrofik Kaynamalarda İntramedüller Çivi Sonuçlarımız
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi